EXPLORING THE DIGITAL LITERACY OF PRE-SERVICE TEACHERS: A STUDY ON THE TEACHING ASSISTANCE PROGRAM - Nur Hafizhah; Nanik Mariani; Fahmi Hidayat (Wiralodra English Journal, 2024)
In today's educational landscape, digital literacy has emerged as a critical skill for pre-service teachers, enabling them to effectively utilize technology in classrooms and provide students with valuable information technology resources. This study aims to investigate the digital literacy levels of pre-service teachers participating in a teaching assistance program at school. Employing descriptive statistics, the research analyzed data collected from pre-service teachers enrolled in the Teaching Assistance Program, using a framework designed to assess teacher digital literacy across five key dimensions: information management, team-based learning, information processing and presentation, digital integrity, and social responsibility. The findings reveal that pre-service teachers demonstrated a high level of digital literacy across all dimensions. While highlighting their readiness to employ information and communications technology (ICT) for educational purposes, the results also underscore an ongoing need for further development in digital literacy skills. Importantly, these findings contribute significantly to providing insightful data regarding the level of digital literacy of pre-service teachers. Next, future research endeavors should address the limitations of this study by employing diversified methodologies and ensuring broader sample representations.